A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India - Muthukatturaja, Marimuthu; Balasubramanian, Chellaiah (Zootaxa, 2021)
A new mayfly species Caenis maduraiensis sp. nov. is described and illustrated from nymph and adults collected from lentic habitat around Madurai. The nymph can be distinguished by the following characters: anterior margin of labrum with row of bipectinate setae longer laterally and a group of highly fringed setae behind emargination; and hind claw long, slender and hooked with row of denticles. Adults are characterized by prosternal triangle with slightly concave sides, tip acutely pointed; apical part of forceps abruptly narrowed to the tip, with a long apical spine, and few trichomes on surface.